2021
DOI: 10.1371/journal.pcbi.1008765
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of selection against centrosome amplification in human cell lines

Abstract: The presence of extra centrioles, termed centrosome amplification, is a hallmark of cancer. The distribution of centriole numbers within a cancer cell population appears to be at an equilibrium maintained by centriole overproduction and selection, reminiscent of mutation-selection balance. It is unknown to date if the interaction between centriole overproduction and selection can quantitatively explain the intra- and inter-population heterogeneity in centriole numbers. Here, we define mutation-selection-like m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
(94 reference statements)
2
8
0
Order By: Relevance
“…However, given the high-throughput data-driven approach deployed in this study, and the large amount of imaging data collected (>10,000 images across >300 FFPE tissues), we did not further inspect individual tissue regions for loss of centrosomes. Neverthless, consistent with the previous study 26 , we observed large variability in the spread of CA scores across all imaging fields within the same tissue, confirming that the CA phenotype displays marked inter-and intra-tissue heterogeneity in HGSOC tumours 22,26 . Both the high degree of CA heterogeneity and the confounding effect of stromal cells underscore the importance of acquiring multiple imaging fields per tumour sample and highlight a key strength of our imaging approach (see Supplementary Methods).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, given the high-throughput data-driven approach deployed in this study, and the large amount of imaging data collected (>10,000 images across >300 FFPE tissues), we did not further inspect individual tissue regions for loss of centrosomes. Neverthless, consistent with the previous study 26 , we observed large variability in the spread of CA scores across all imaging fields within the same tissue, confirming that the CA phenotype displays marked inter-and intra-tissue heterogeneity in HGSOC tumours 22,26 . Both the high degree of CA heterogeneity and the confounding effect of stromal cells underscore the importance of acquiring multiple imaging fields per tumour sample and highlight a key strength of our imaging approach (see Supplementary Methods).…”
Section: Discussionsupporting
confidence: 91%
“…Most studies that have investigated mechanisms and consequences of CA have experimentally induced or inhibited CA in cell lines or other model systems predominantly in breast cancer models. However, the high degree of variability in centrosome numbers observed across cancer cell populations indicates the existence of a CA “set point” or equilibrium 22 and suggests that cell lines have different tolerance thresholds for CA and maintain centrosome numbers through an equilibrium of CA mechanisms and negative selection 23,24 . Consequently, the experimental induction or inhibition of CA may trigger a range of different cellular responses that would not otherwise be observed without these artificial perturbations.…”
Section: Introductionmentioning
confidence: 99%
“…The balance of cells with CA in the population is maintained dynamically. A recent study by Dias Louro and colleagues ( 110 ) employed a model selection approach to infer patterns of CA and selection in a diverse panel of human cancer cell lines. Their results indicate that the fraction of cells with CA in these populations is at equilibrium, and maintained by a balance of centrosome overproduction and negative selection (apoptosis) of cells with CA, reminiscent of mutation-selection balance.…”
Section: Discussionmentioning
confidence: 99%
“…Conceivably, centrosome amplification can promote tumorigenesis in mouse models [ 58 ], but evidence for the lack of such an effect also exists [ 59 ]. This apparent controversy likely results at least in part from strong selection against extra centrioles in proliferating cells [ 60 ].…”
Section: Discussionmentioning
confidence: 99%